GRILLING AND HEALTH: ANALYZING POLYCYCLIC AROMATIC HYDROCARBONS IN SMOKED FISH FROM TOGO - Mensah , Kwame Nkrumah (Ayden Journal of Agriculture and Allied Studies, 2024)
Smoking has long been practiced as a method of food preservation in various regions, particularly for meats, fish, and cheeses. This traditional technique combines smoking with processes like cooking, drying, and salting, imparting not only preservation benefits such as dehydration, bactericidal action, and antioxidant properties but also enhancing flavor and color (Rivier et al., 2009; Škaljac et al., 2018). Smoking fish, in particular, remains a prevalent preservation method in many developing countries (Adeyeye and Oyewole, 2016a). In West African nations, artisanal fishery plays a significant role in the local economy, with approximately 40% of products undergoing smoking before consumption (FAO, 2009a). Coastal areas heavily rely on fish processing, providing stable employment opportunities (Adeyeye and Oyewole, 2016b; Nyebe et al., 2014). Fish, as a source of animal protein, holds great importance in the West African coastal region, constituting a substantial proportion of dietary protein intake, especially in countries like Senegal, Gambia, Sierra Leone, and Ghana (Béné and Heck, 2005). Smoked fish, in particular, is readily available and affordable for both rural and urban low-income households, making it a vital protein source when compared to the relatively expensive meat (FAO, 2009b).